Interactive e-government - Ali, Muhammad Shahbaz; Vaquer, John C. (2008)
The use of information technology has been one of the core elements in transforming the way government interacts with its constituents. E- government and the delivery of e-services from government are changing the way government governs and interacts with its citizenry. This study was designed to take a descriptive look at how three local municipalities in northern Sweden are coping with trying to be more interactive with the delivery of e-services from the perspective of the direct service provider. The study examines the current state and the willingness of local government to implement a more interactive website format for the delivery of e-services. The overall conclusion is that that the delivery of e- services and the growth and maturity of e-government is being adopted by the municipalities, but all are at the early stages of development and implementation. E-services delivery is present but the sophistication is still in its infancy when used by local governments. Most local governments only provide published information and downloadable forms. Most local government sites provide only one way communications. All are still at the basic level of publishing information online but little two-way communication exists between the service provider and the citizen user. Delivery of e-services for local government services is far from being mastered by the service providers. It’s particularly lacking attention on making the services more interactive. There is a strong need to develop and implement more effective two way communications between the provider of e-services and the user. Validerat; 20101217 (root)